2011
DOI: 10.3233/jad-2011-101815
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Cytokines in the Brains of Alzheimer's Disease (AD) Patients Compared to the Brains of Non-Demented Patients with and without Increasing AD Pathology

Abstract: Neuroinflammation is involved in the Alzheimer’s disease (AD) pathology. Our major focus was to clarify whether neuroinflammation plays important roles in AD pathogenesis, particularly prior to the manifestation of overt dementia. We analyzed cytokine expression profiles of the brain, with focus on non-demented patients with increasing AD pathology, referred to as high pathology control (HPC) patients, who provide an intermediate subset between AD and normal control subjects, referred to as low pathology contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 58 publications
1
54
0
1
Order By: Relevance
“…Cytokine profiles in the brain are altered in AD. A recent study demonstrated that IL-1β, IL-10, IL-13, IL-18, IL-33, TGF-β1, and TNF-α converting enzyme are elevated in AD [37]. In the Tg2576 model, TNF-α, IL-1β, and MCP-1 are increased with age and plaque deposition [38].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine profiles in the brain are altered in AD. A recent study demonstrated that IL-1β, IL-10, IL-13, IL-18, IL-33, TGF-β1, and TNF-α converting enzyme are elevated in AD [37]. In the Tg2576 model, TNF-α, IL-1β, and MCP-1 are increased with age and plaque deposition [38].…”
Section: Discussionmentioning
confidence: 99%
“…For example in areas with dense plaque accumulations C1q mRNA increased from 11 to 80 fold compared to normal AD brain (Yasojima et al 1999). In addition pro-inflammatory cyokines, for example the interleukins and TNF␣, have been shown to have increased expression (Morimoto et al 2011). This may constitute a driving force in stimulating local complement protein production.…”
Section: Are Measurements Of Complement Gene Expression Useful As a Bmentioning
confidence: 97%
“…41,42 Nevertheless, extended treatment of asymptomatic individuals with the anti-inflammatory drug naproxen reduced the incidence of AD, supporting a beneficial effect of anti-inflammatory drugs only when administered in early, asymptomatic phases of the disease. 43 Interestingly, patients with high plaque burden without dementia-so-called high-pathology controls 44,45 show almost no evidence of neuroinflammation [46][47][48] and neuro degeneration. 46 These findings are in accordance with results from several transgenic mouse lines that express human versions of AD-inducing mutated genes, which show no evidence of strong neuroinflammatory responses nor widespread progressive neuronal cell death.…”
Section: Inflammation-a Key Playermentioning
confidence: 99%